Performing and Interpreting Fractional Flow Reserve Measurements in Clinical Practice: An Expert Consensus Document - Achenbach, Stephan; Rudolph, Tanja; Rieber, Johannes; Eggebrecht, Holger; Richardt, Gert; Schmitz, Thomas; Werner, Nikos; Boenner, Florian; Möllmann, Helge (Interventional Cardiology (London), 2017)
Fractional flow reserve (FFR) measurements can determine the haemodynamic relevance of coronary artery stenoses. Current guidelines recommend their use in lesions in the absence of non-invasive proof of ischaemia. The prognostic impact of FFR has been evaluated in randomised trials, and it has been shown that revascularisation can be safely deferred if FFR is >0.80, while revascularisation of stenoses with FFR values ≤0.80 results in significantly lower event rates compared to medical treatment. Left main stenoses, aorto-ostial lesions, as well as patients with left ventricular hypertrophy and severely-impaired ejection fraction, have been excluded from large, randomised trials. While FFR measurements are relatively straightforward to perform, uncertainty about procedural logistics, as well as data acquisition and interpretation in specific situations, could explain why they are not widely used in clinical practice. We summarise the clinical data in support of FFR measurements, and provide recommendations for performing and interpreting the procedure.
EVALuna2:36039